Evaluation of Glutathione in Spike Protein of SARS-CoV-2 Induced Immunothrombosis and Cytokine Dysregulation - Brandon Norris; Abraham Chorbajian; John Dawi; Aishvaryaa Shree Mohan; Ira Glassman; Jacob Ochsner; Yura Misakyan; Arbi Abnousian; Anthony Kiriaki; Kayvan Sasaninia; Edith Avitia; Cesar Ochoa; et al. (MDPI AG, 2024)
Thrombotic microangiopathy has been identified as a dominant mechanism for increased mortality and morbidity in coronavirus disease 2019 (COVID-19). In the context of severe COVID-19, patients may develop immunothrombosis within the microvasculature of the lungs, which contributes to the development of acute respiratory distress syndrome (ARDS), a leading cause of death in the disease. Immunothrombosis is thought to be mediated in part by increased levels of cytokines, fibrin clot formation, and oxidative stress. Glutathione (GSH), a well-known antioxidant molecule, may have therapeutic effects in countering this pathway of immunothrombosis as decreased levels of (GSH) have been associated with increased viral replication, cytokine levels, and thrombosis, suggesting that glutathione supplementation may be therapeutic for COVID-19. GSH supplementation has never been explored as a means of treating COVID-19. This study investigated the effectiveness of liposomal glutathione (GSH) as an adjunctive therapy for peripheral blood mononuclear cells (PBMC) treated with SARS CoV-2 spike protein. Upon the addition of GSH to cell cultures, cytokine levels, fibrin clot formation, oxidative stress, and intracellular GSH levels were measured. The addition of liposomal-GSH to PBMCs caused a statistically significant decrease in cytokine levels, fibrin clot formation, and oxidative stress. The addition of L-GSH to spike protein and untreated PBMCs increased total intracellular GSH, decreased IL-6, TGF-beta, and TNF-alpha levels, decreased oxidative stress, as demonstrated through MDA, and decreased fibrin clot formation, as detected by fluorescence microscopy. These findings demonstrate that L-GSH supplementation within a spike protein-treated PBMC cell culture model reduces these factors, suggesting that GSH supplementation should be explored as a means of reducing mediators of immunothrombosis in COVID-19.